The Statues and Plants and Animals in Bumiayu Temples Region Tanah Abang Sub District, Penukal Abab Ilir Regency - Sondang M Siregar (Research Centre of Inorganic Materials and Complexs, 2018)
The area of ??percandiaan Bumiayu dates from the 9th century AD. Inside the site there are 5 temples that have been restored (shown) that are temples 1,2,3,7 and 8 and 6 temples are still buried in the soil that is temple 4,5,6,8,9,10, 11. temple building Bumiayu condition now live foot of the temple, although with the findings of roof components and body of the temple around the temple yard show the temple 1, 2 and 3 was once a complete building consisting of the roof, body and foot of the temple. In Temple 1 and 3 Bumiayu illustrated fauna in the form of statues and reliefs. While the picture of the flora found in the temple reliefs 1.3 and 8. The problems that arise are the types of flora and fauna of what is described on the statue and reliefs in the area Percandiaan Bumiayu and whether the flora and fauna describes the environmental settings Bumiayu site. The purpose of writing is to know the types of flora-fauna described on the statue and reliefs in the area percandiaan Bumiayu and to know the environmental conditions in the area percandiaan Bumiayu. The method used is qualitative method with descriptive-explanative analysis especially to analyze flora-fauna shape which is depicted on statue and relief in percandiaan Bumiayu area. The results showed that the area of ??percandiaan Bumiayu belongs to mixed dipterocarp forests which belong to the rain forest biomes which are always wet to dry with sub-biomes of dry land rain forest. The depiction of flora reliefs such as Kalpataru trees and lotus flowers and relief fauna such as snakes, parrots, monkeys, crocodiles and turtles show the ancient forest ecosystem of Bumiayu and the flora and fauna are still found in the forest of Bumiayu until now.